Photo-stimulatory effect of low energy helium-neon laser irradiation on excisional diabetic wound healing dynamics in wistar rats - Maiya Arun; Kumar Pramod; Nayak Shivanand (Wolters Kluwer Medknow Publications, 2009)
Background: Generally, the significances of laser photo stimulation are now accepted, but the laser light facilitates wound healing and tissue repair remains poorly understood. Aims: We have examined the hypothesis that the laser photo stimulation can enhance the collagen production in diabetic wounds using the excision wound model in the Wistar rat model. Methods: The circular wounds were created on the dorsum of the back of the animals. The animals were divided into two groups. The study group (N = 24) wound was treated with 632.8 nm He-Ne laser at a dose of 3-9J/cm 2 for 5 days a week until the wounds healed completely. The control group was sham irradiated. Result: A significant increase in the hydroxyproline content and reduction in the wound size were observed in the study group. The pro-healing actions seem to be due to increased collagen deposition as well as better alignment and maturation. Conclusion: The biochemical analysis and clinical observation suggested that 3-6 J/cm 2 laser photo stimulation facilitates the tissue repair process by accelerating collagen production in diabetic wound healing.